The policy of Great Britain regarding Australia, 1850-1900 - Teniswood, W. V. (The University of Edinburgh, 1936)
This thesis deals with some aspects of the policy of Great Britain in her relations with the Australian colonies during the second half of the 19th Century. The chief colonial problems of the 19th Century were connected with the land system, transportation and immigration; trade, tariffs and communications; defence; self - government and the Imperial connection. As far as Australia was concerned, there was no native problem. I have not attempted to deal with the first group as that would have involved a detailed examination of the history of the colonies prior to 1850 and resulted in an unduly long thesis. I have tried to show the policy of the British Government towards self- government and the Imperial connection by describing the steps by which responsible government was acquired in each of the states and by an account of the movement which resulted in the federation of those states. The account of the first three Colonial Conferences seemed to be the best way to exemplify Great Britain's policy with regard to trade, tariffs, communications and defence. Chapter III, on the general attitude of Great Britain towards the colonial empire, is intended to be representative and typical rather than exhaustive and to give in a general way some idea of the evolution of colonial policy in the 19th Century.